Repeatability of total Keratometry and standard Keratometry by the IOLMaster 700 and comparison to total corneal astigmatism by Scheimpflug imaging - Savini, Giacomo; Taroni, Leonardo; Schiano-Lomoriello, Domenico; Hoffer, Kenneth J. (Eye (London), 2021)
Objectives We aimed (1) to assess the repeatability of Total Keratometry (TK) and standard keratometry (K) measurements, as provided by the IOLMaster 700 (Carl Zeiss Meditec), and (2) to compare the corneal astigmatism measured by TK to the total corneal astigmatism (TCA) measured by a Scheimpflug camera (Pentacam AXL, Oculus). Methods Two groups of patients were prospectively enrolled: Group A included previously unoperated eyes undergoing cataract surgery, and Group B eyes with previous myopic corneal excimer laser surgery. TK and K were measured three times by the same examiner. Repeatability was assessed based on the within-subject standard deviation ( S w ), test–retest variability, coefficient of variation and intraclass correlation coefficient (ICC). In Group A, TCA was measured once and compared to TK astigmatism. Vector analysis was performed according to Næser. Results In Group A (69 eyes) the mean K and TK were, respectively, 43.14 ± 1.37 D and 43.18 ± 1.37 D. In Group B (51 eyes) the mean K and TK were, respectively, 40.14 ± 2.20 D and 39.71 ± 2.35 D. The repeatability of the average K and TK was high ( S w < 0.10D). All measurements revealed an ICC > 0.9. For most measurements the variance of K and TK did not show any statistically significant difference either within groups or between groups. Vectors KP(45) were significantly different between TK astigmatism and TCA. Conclusions TK measurements offer high repeatability in unoperated and post-excimer laser surgery eyes. TK astigmatism and TCA measurements could not be considered interchangeable.